2016
DOI: 10.1016/j.energy.2016.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low gravity on water removal inside proton exchange membrane fuel cells (PEMFCs) with different flow channel configurations

Abstract: a b s t r a c tPractically investigate water removal and cell performance for PEMFCs under low gravity circumstance is an urgent task, especially as a promising power supply unit applied to space engineering. PEMFC with an in-situ optical flow field was used to explicate two-phase flow and water removal inside cathode flow field from terrestrial gravity to microgravity. The cell was tested in the vertical and horizontal flow channel orientations. A 3.6 s short-time micro-gravity circumstance was provided by Na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…The two‐phase flow in gas channels can be affected by factors such as flow rate, humidity, [ 43,45 ] channel dimensions and profiles (parallel, serpentine, and interdigitated), [ 46,47 ] temperature, current density, [ 48 ] gas diffusion layer (GDL) materials, [ 49 ] and gravitational orientations. [ 50 ] Zhan et al. found that the generation of water on the electrode is not uniform with a higher production rate under the channel backs than that in channel.…”
Section: Optical Microscopy Studies Of Polymer Electrolyte Membrane Fmentioning
confidence: 99%
“…The two‐phase flow in gas channels can be affected by factors such as flow rate, humidity, [ 43,45 ] channel dimensions and profiles (parallel, serpentine, and interdigitated), [ 46,47 ] temperature, current density, [ 48 ] gas diffusion layer (GDL) materials, [ 49 ] and gravitational orientations. [ 50 ] Zhan et al. found that the generation of water on the electrode is not uniform with a higher production rate under the channel backs than that in channel.…”
Section: Optical Microscopy Studies Of Polymer Electrolyte Membrane Fmentioning
confidence: 99%
“…In addition, it was observed during the experiments that the fuel cell was more difficult to restart when it had remained stored for a long time at room temperature and that it had to be purged much more regularly to be able to restart it. It could be due to flooding as it has been observed that water flooding in PEMFCs is gravity dependent [61].…”
Section: Figure 4: Effects Of the Calendar Aging On The Performance Omentioning
confidence: 99%
“…In PEMFC, water is produced as hydrogen is consumed in the electrochemical reaction. Liquid water, if not removed effectively, will block the porous catalyst layer (CL) and gas diffusion layer (GDL), as well as the gas flow channel in the cathode of PEMFC . The so‐called water flooding impedes reactant transport to the reaction sites and hence causes severe PEMFC performance degradation.…”
Section: Introductionmentioning
confidence: 99%
“…Liquid water, if not removed effectively, will block the porous catalyst layer (CL) 2 and gas diffusion layer (GDL), 3,4 as well as the gas flow channel in the cathode of PEMFC. 5 The so-Nomenclature: D droplet , water droplet diameter (m); f , volume fraction of the fluid; F s , external force term (N m −3 ); g, gravitational force (m s −2 ); n, surface normal; b n, surface unit normal; P, pressure (Pa); t, time; b t, surface unit tangent; T B , the breaking off time (ms); T D , the detaching time (ms); T L , the landing time (ms); T T , the touching time (ms); v, velocity component (m s −1 ); V, velocity vector (m s −1 ) Subscripts/Superscripts: 0, initial; 1, 2, liquid water, air; c, capillary force; channel, flow channel surface; GDL, GDL surface; lg, liquid-gas interface; needle, needle; s, source term or suspension; T, transpose; w, wall; x, y, z, axes Greeks: α needle , the needle inclination angle (°); ΔT c , the needle capillary force duration (ms); ΔT s , the water suspension time (ms); θ, contact angle (°); κ, surface curvature; μ, viscosity (kg m −1 s −1 ); ρ, density (kg m −3 ); σ, surface tension coefficient (N m −1 ) called water flooding impedes reactant transport to the reaction sites and hence causes severe PEMFC performance degradation. To improve water removal from PEMFC, effective water management strategies, which include the design of fuel cell operating conditions, geometric parameters, and surface wettability, need to be implemented in PEMFC.…”
Section: Introductionmentioning
confidence: 99%